Resource stoichiometry and availability modulate species richness and biomass of tropical litter macro‐invertebrates. (19th June 2017) - Jochum, Malte; Barnes, Andrew D.; Weigelt, Patrick; Ott, David; Rembold, Katja; Farajallah, Achmad; Brose, Ulrich
Abstract: High biodiversity and biomass of soil communities are crucial for litter decomposition in terrestrial ecosystems such as tropical forests. However, the leaf litter that these communities consume is of particularly poor quality as indicated by elemental stoichiometry. The impact of resource quantity, quality and other habitat parameters on species richness and biomass of consumer communities is often studied in isolation, although much can be learned from simultaneously studying both community characteristics. Using a dataset of 780 macro‐invertebrate consumer species across 32 sites in tropical lowland rain forest and agricultural systems on Sumatra, Indonesia, we investigated the effects of basal resource stoichiometry (C:X ratios of N, P, K, Ca, Mg, Na, S in local leaf litter), litter mass (basal resource quantity and habitat space), plant species richness (surrogate for litter habitat heterogeneity), and soil pH (acidity) on consumer species richness and biomass across different consumer groups (i.e. 3 feeding guilds and 10 selected taxonomic groups). In order to distinguish the most important predictors of consumer species richness and biomass, we applied a standardised model averaging approach investigating the effects of basal resource stoichiometry, litter mass, plant species richness and soil pH on both consumer community characteristics. This standardised approach enabled us to identify differences and similarities in the magnitude and importance of such effects on consumer species richness and biomass. Across consumer groups, we found litter mass to be the most important predictor of both species richness and biomass. Resource stoichiometry had a more pronounced impact on consumer species richness than on their biomass. As expected, taxonomic groups differed in which resource and habitat parameters (basal resource stoichiometry, litter mass, plant species richness and pH) were most important for modulating their community characteristics. The importance of litter mass for both species richness and biomass indicates that these tropical consumers strongly depend on habitat space and resource availability. Our study supports previous theoretical work indicating that consumer species richness is jointly influenced by resource availability and the balanced supply of multiple chemical elements in their resources. Abstract : While effects of resource quantity, quality and other habitat parameters on consumer species richness and biomass are often studied in isolation, the authors used a standardised model averaging framework to simultaneously investigate effects on macro‐invertebrate consumer communities in tropical leaf litter. Litter mass and resource stoichiometry dominated both consumer community characteristics.